Nucleoside analogs as a rich source of antiviral agents active against arthropod-borne flaviviruses - Eyer, Luděk; Nencka, Radim; de Clercq, Erik; Seley-Radtke, Katherine; Růžek, Daniel (Antiviral chemistry & chemotherapy, 2018)
Nucleoside analogs represent the largest class of small molecule-based antivirals, which currently form the backbone of chemotherapy of chronic infections caused by HIV, hepatitis B or C viruses, and herpes viruses. High antiviral potency and favorable pharmacokinetics parameters make some nucleoside analogs suitable also for the treatment of acute infections caused by other medically important RNA and DNA viruses. This review summarizes available information on antiviral research of nucleoside analogs against arthropod-borne members of the genus Flavivirus within the family Flaviviridae, being primarily focused on description of nucleoside inhibitors of flaviviral RNA-dependent RNA polymerase, methyltransferase, and helicase/NTPase. Inhibitors of intracellular nucleoside synthesis and newly discovered nucleoside derivatives with high antiflavivirus potency, whose modes of action are currently not completely understood, have drawn attention. Moreover, this review highlights important challenges and complications in nucleoside analog development and suggests possible strategies to overcome these limitations.
Keywords: inhibitor; antiviral agent; Nucleoside analog; Nucleosides; molekulární struktura; Molecular Structure; antivirové látky; nukleosidy; Microbial Sensitivity Tests; antiviral therapy; Flavivirus Infections; arthropod-borne flavivirus; Animals; Antiviral Agents; Flavivirus; infekce viry z rodu Flavivirus; zvířata; mikrobiální testy citlivosti; Culicidae